Effects of dietary Bacillus velezensis Y01 supplementation on growth performance, immune function, and cecal microbiota of 1 to 42 days Langya chickens - Lumin Yu; Lingling Zhang; Shanpeng Zhang; Yuzhong Zhao; Zhihao Bi; Junye Xu; Hongcheng Fu; Xinglin Zhang (BMC Microbiology)
Abstract Bacillus velezensis (B. velezensis) has gained increasing recognition as a probiotic for improving animal growth performance and intestinal health. However, whether B. velezensis affects growth performance, immune function, and cecal microbiota in Chinese local breeds of chickens remains unclear. In this study, a total of 180 one-day-old healthy male Langya chicks were randomly divided into 3 treatment groups with 5 replicates per group and 12 chicks each replicate. Langya chicks were fed with a corn-soybean-based diet as the control group (CON), and 2 other groups were fed the same basal diet supplemented with 50 mg/kg aureomycin or 2.0 × 109 CFU/kg B. velezensis Y01 as the antibiotic-treated group (ANT) and the B. velezensis-treated group (BVT), respectively, for 42 days. Dietary supplementation with B. velezensis Y01 resulted in a 7.01% increase in the final body weight, a 7.27% increase in weight gain (WG), and a 7.24% increase in average daily gain (ADG) in Langya chickens at 42 days of age in the BVT group when compared to the CON group (p < 0.05). Meantime, the final body weight was increased by 5.88%, WG by 6.18%, and ADG by 6.19% in the BVT group when compared to the ANT group (p < 0.05). The BVT group with B. velezensis Y01 resulted in a 26.80% decrease in lactate dehydrogenase (LDH), a 52.92% decrease in uric acid (UA), a 20.70% decrease in cholesterol (CH), and a 40.84% decrease in urea when compared to the CON group (p < 0.05). Furthermore, the serum immunoglobulin G (IgG) levels were increased by 36.09%, IgM by 56.08%, and interleukin-2 (IL-2) by 32.83% in the BVT group in comparison to the CON group (p < 0.05), but IL-1, IL-6, and tumor necrosis factor-α (TNF-α) levels had no changes (p > 0.05). Notably, B. velezensis Y01 enriched the abundance of Firmicutes and Bacteroidetes, resulting in the production of certain beneficial metabolites that play pivotal roles in reducing the abundance of harmful bacteria. This, in turn, decreases the virulence genes and antibiotic resistance genes in the cecal microbial communities, ultimately enhancing immunity and metabolism in Langya chickens. Collectively, these results are encouraging and suggesting that B. velezensis Y01 may be an effective alternative of antibiotic growth promoters for improving chickens’ growth performance and intestinal health in poultry production.